The Evaluation of Nurse Workload in the General Surgery Ward at Puruk Cahu Regional General Hospital - Khalifah, Sarini; Tasalim, Rian; Wijaksono, M. Arief; Rahman, Subhannur; Irwansyah, Irwansyah (PROMOTOR, 2025)
The workload of nurses in general surgery wards is a crucial issue in hospital nursing management, especially in high-intensity units. A high workload can affect the quality of care and the health of nurses. Nurses who experience a high workload are prone to physical and mental fatigue, which can impact patient safety. This study aims to evaluate the workload of nurses in the general surgery ward at Puruk Cahu Regional General Hospital. This is a descriptive quantitative study with a cross-sectional approach. Data were collected using a questionnaire that had been tested for validity and reliability. The sample consisted of 23 nurses working in the general surgery ward at Puruk Cahu Regional General Hospital, using the total sampling method. Data analysis was performed using descriptive statistics to evaluate the frequency distribution and workload. The majority of nurses (65.2%) experienced a moderate workload, while 21.7% experienced a high workload. A moderate workload allows nurses to work efficiently, but nurses with a high workload are at significant risk of fatigue. Additionally, permanent nurses dominated the staff (60.9%), and 39.1% of the nurses had 1-5 years of work experience. A moderate workload is an ideal condition for most nurses to maintain the quality of care. However, high workloads require more attention from hospital management to prevent fatigue and burnout. Regular workload evaluations and management strategies that support nurse well-being are needed.